A Comparative Study of The Relationship Between Religion and Science in The Qur'an and The Bible - Adzim, M Bintang Fauzil; Khasanah, Ismiyatul; Wulandari, Ayu; Meilani, Aisyah; Ardhani, Sabrina Naura; Anwar, M Ariq; Saniyah, Adilah (International Tatho Academics, 2025)
This study examines Dondy Tan's thoughts on the existence of science in Islam and the Bible. This study seeks to identify Dondy Tan's concepts, arguments, and approaches in understanding the existence and role of science in Islam and the Bible. The research method used is a qualitative approach in the form of media observation studies. The results of the study show that Dondy Tan's view of science in the perspective of the Qur'an can be seen as an integrative relationship between science and the Qur'an (Islam), whereas in the perspective of the Bible, according to Dondy Tan, it tends to show a conflicting relationship between science and religion. This study contributes to the importance of an interdisciplinary approach through contextual and historical readings in understanding the relationship between religion and science.